The Relationship between Organizational Happiness and Job Motivation with Turnover Intention of Health Centers Staff - Ali Sadeghi; Azam Alavi (Journal of Social Behavior and Community Health, 2023)
Background: Understanding the factors affecting turnover intention as one of the challenges of health care organizations is vital to retain employees. This study aims to investigate the relationship between organizational happiness and job motivation with turnover intention of health centers staff. Methods: This descriptive-analytical correlational study was conducted on 148 employees of health centers according to Cochran formula by convenience sampling method in Chaharmahal and Bakhtiari province in the first half of 2020. Data were collected using three standard questionnaires including organizational happiness, Herzberg's job motivation questionnaire (1959), and turnover intention. Statistical analyses were done by descriptive and analytical statistics using SPSS v.24. Results: There was a significant relationship between the mean score of organizational happiness and job motivation with turnover intention (P < 0.001). A significant relationship was also found between the mean score of employees' organizational happiness and turnover intention (r = 0.506 ،p > 0.001). The results showed a significant relationship between the mean score of employees' job motivation with turnover intention (r = 0.506 ، p > 0.001). Conclusion: Organizational happiness and job motivation are directly and positively related to turnover intention. It is suggested that relevant authorities strengthen the areas of fostering organizational happiness and job motivation of health workers to provide a stronger basis to reduce their turnover intention.